Correlation between UGT1A1 polymorphism and efficacy and toxicity of irinotecan in Chinese cancer patients - Shuai Geng; Yulong Shen; Chen Zhang; Nan Wang; Xinyue Gao; Xinyu Luo; Ning Shi (Frontiers in Pharmacology)
ObjectiveTo assess the association between UGT1A1*6/*28 polymorphisms and Irinotecan (IRI) efficacy/toxicity in Chinese cancer patients.MethodWe systematically searched PubMed, Cochrane, CNKI, and Wanfang databases. Two investigators independently conducted literature screening, data extraction, and meta-analysis using Revman 5.4.ResultsThis study included 19 clinical trials or case-control studies, with a total of 1,698 patients. Meta-analysis showed that, ① There was no correlation between UGT1A1*6 or UGT1A1*28 gene polymorphism and IRI efficacy; ② UGT1A1*6 or UGT1A1*28 gene polymorphisms are associated with grade 3–4 diarrhea, grade 3–4 neutropenia, and grade 3–4 leukopenia, and the above-mentioned toxic reactions are more common in wild types (GG and TA6/6). ③ There was no correlation between UGT1A1*6 and UGT1A1*28 mutations and the efficacy of IRI; ④ The double wild type was more prone to grade 0–2 neutropenia, the single-site variant was more prone to grade 0–2 diarrhea, and the double-site variant was more prone to grade 3–4 neutropenia, but none of them were related to leukopenia.ConclusionUGT1A1*6/*28 polymorphisms predict IRI-induced toxicity severity but not therapeutic efficacy in Chinese patients. These variants may serve as predictive biomarkers for personalized IRI chemotherapy.